The Dynamics Of Criminogenic Organizational Within The Financial Crime In Indonesia - Supriyanto, Supriyanto; Meliala, Adrianus E.; Sulhin, Iqrak (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The criminogenic organizational dynamics within the financial crime of Indonesia are reflected in the increased criminality cases from 2012 to 2020. Criminogenic organizations support the situations for both corporations and individual corporations to commit their crimes. This research identified the contributions of the criminogenic organizational aspect of financial crime in Indonesia. The applied method was the qualitative grounded theory. The researchers took the cases occurring within the period of 2012 and 2020. Then, the researchers comprehended the primary data with in-depth interviews. The researchers found the criminogenic organizational indicators within the corporate crimes were: profit-oriented ambition, expansion, and domination; business continuity and individual 'secured' position; fear of failure to reach the target; certain group loyalty; ethical perception and business morals; the bias of responsibility distribution; and tendency to promote ethnocentric approach. The results could be the initial stage to composing criminal policy in preventing corporate crime by prioritizing the corporate cultures with excellent corporate ethics.